2019
DOI: 10.1038/s41586-019-1242-z
|View full text |Cite
|
Sign up to set email alerts
|

A cool accretion disk around the Galactic Centre black hole

Abstract: A supermassive black hole Sagittarius A* (SgrA*) with the mass M SgrA * 4 × 10 6 M resides at the centre of our galaxy [1,2]. A large reservoir of hot (10 7 K) and cooler (10 2 − 10 4 K) gas surrounds it within few pc [3]. Building up such a massive black hole within the ∼ 10 10 year lifetime of our galaxy would require a mean accretion rate of ∼ 4 × 10 −4 M yr −1 . At present, X-ray observations constrain the rate of hot gas accretion at the Bondi radius (10 5 R Sch = 0.04 pc at 8 kpc) tȯ M Bondi ∼ 3 × 10 −6 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 42 publications
17
84
1
Order By: Relevance
“…1 and 6), hydrogen gets excited and the depletion of [FeIII] from the dust grains of the dusty sources is increased. Upcoming observations with MIRI and long term monitoring with SIN-FONI on larger scales of these sources and the GC will probably reveal more interesting details about the connection of the Sgr A* bubble, the wind, the in Murchikova et al (2019) presented Doppler-shifted Brγ emission, and the presented north-to south Brγ-bar. These observations becoming more important in the future since some dusty sources, e.g., D2 and D3 are moving in projection towards regions, where no wind features are present.…”
Section: [Feiii] Distribution In the Galactic Center Around Sgr A*mentioning
confidence: 95%
“…1 and 6), hydrogen gets excited and the depletion of [FeIII] from the dust grains of the dusty sources is increased. Upcoming observations with MIRI and long term monitoring with SIN-FONI on larger scales of these sources and the GC will probably reveal more interesting details about the connection of the Sgr A* bubble, the wind, the in Murchikova et al (2019) presented Doppler-shifted Brγ emission, and the presented north-to south Brγ-bar. These observations becoming more important in the future since some dusty sources, e.g., D2 and D3 are moving in projection towards regions, where no wind features are present.…”
Section: [Feiii] Distribution In the Galactic Center Around Sgr A*mentioning
confidence: 95%
“…where M d is the mass of the disk. Thus, for the cold disk, with M d ∼ 10 −4 − 10 −5 M (Murchikova et al 2019) the timescale due to accretion is rather long, depicted in Figure 4 as a grey band. For the hot component we adopt M d ∼ 10 −9 M .…”
Section: The Time Variability Of a Stellar Orbitmentioning
confidence: 99%
“…This accretion model seems to be consistent with the observed spectrum of Sgr A* and may yield high temperature for the plasma, (∼ 10 12 K and ∼ 10 9 K for the ions and electrons, respectively, e.g., Narayan et al 1998). Recently, Murchikova et al (2019) reported the detection of a cool (∼ 10 4 K) rotationally supported disk, embedded within the hot plasma. Below we adopt a two component model in order to investigate the consequences of a companion on SgrA* under a broad range of external conditions.…”
Section: The Time Variability Of a Stellar Orbitmentioning
confidence: 99%
“…The second key science driver proposed in Mroczkowski et al (2019a) is to probe the origins of chemical complexity, one of the key science goals identified in the ALMA 2030 Development These include the ground state transitions of deuterated dense gas probing species which trace the cold, quiescent regions at the cusp of star formation and complex organic molecules that can trace building blocks of life (including amino acids such as glycene), which at these lower frequencies are easier to identify due to the lower spectral-crowding. In addition, this frequency range is rich in recombination lines of hydrogen (see Murchikova et al 2019 and the discussion in Mroczkowski et al 2019a), along with tracers of the chemical evolution of stars and stellar envelopes, to name a few. As with the above case, the molecular lines found in Band 2 are often due to ground state transitions, meaning they are brighter and that they leverage abundances directly.…”
Section: Molecular/chemical Complexity In the Milky Way Galaxymentioning
confidence: 99%